Improved detection of bacterial growth in continuous ambulatory peritoneal dialysis effluent by use of BacT/Alert FAN bottles. - Alfa, M J (1997)
Culture-negative peritonitis is a major complication for patients on continuous ambulatory peritoneal dialysis (CAPD) and precludes organism-specific therapy. The aim of the present study was to compare inoculation of 10 ml of CAPD effluent into BacT/Alert blood culture bottles (FAN [fastidious antimicrobic neutralizing], BacTAlert aerobic [BTA], and BacT/Alert anaerobic [BTAn] bottles) to our conventional method of using 50 ml of concentrated CAPD effluent to inoculate peptone broth bottles (BD bottles) and MacConkey agar and blood agar medium (BA-MAC). The FAN, BTA, and BTAn bottles were monitored automatically in the BacT/Alert blood culture instrument. A total of 207 CAPD effluents were studied, and in 97 bacteria were detected by at least one method. Compared to BTA bottles (79 of 97; 81.4%), BTAn bottles (78 of 97; 80.4%), and BD bottles (88 of 97; 90.7%), the single best broth medium for detecting bacterial growth in CAPD effluents was the FAN bottle (90 of 97 effluents; 92.8%). A total of 125 bacterial species were detected by any method, and the majority (91.8%) of CAPD effluents were infected with a single species. A combination of FAN and BTAn bottles detected 111 of 125 (88.8%) of all organisms, whereas a combination of BD bottles and BA-MAC detected 107 of 125 (85.6%) of all organisms. One or more organisms that would have been completely missed by the conventional method with BD bottles and BA-MAC were detected in 18 CAPD effluents. Of these 18 CAPD effluents, 6 showed no growth by the conventional method with BD bottles and BA-MAC. On the basis of our data, the most sensitive and least labor intensive method was direct inoculation of 10 ml of CAPD effluent into a FAN bottle and a BTAn bottle, which could be automatically monitored by the BacT/Alert blood culture instrument. On the basis of case definitions for peritonitis, the sensitivities and specificities of the methods with FAN and BTAn bottles and with BD bottles and BA-MAC were 81.1 and 98.8% and 74.5 and 96.5%, respectively.